2016
DOI: 10.1108/md-09-2015-0421
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between workplace ostracism and information exchange

Abstract: Purpose The detrimental effect of workplace ostracism on core employee and organizational outcomes has received increasing attention. However, very little is known about its impact on group related outcomes. Given that workplace relationships play a salient role in enhancing employee willingness to share information and knowledge, the present paper examines the link between workplace ostracism and information exchange. In doing so, we also highlight the mediating role of a novel construct, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 72 publications
3
58
0
8
Order By: Relevance
“…In addition, this paper employs cross-sectional data to construct a mediation model, it has been suggested that this approach could generate biased estimates because such models ignore the true longitudinal nature of mediation by not allowing statistical control for prior independent or prior dependent variables (Maxwell et al, 2011). We acknowledge this possibility but indicate that such methods have been employed in other non-related works (Chang, 2015;Gkorezis & Bellou, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this paper employs cross-sectional data to construct a mediation model, it has been suggested that this approach could generate biased estimates because such models ignore the true longitudinal nature of mediation by not allowing statistical control for prior independent or prior dependent variables (Maxwell et al, 2011). We acknowledge this possibility but indicate that such methods have been employed in other non-related works (Chang, 2015;Gkorezis & Bellou, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Job Dissatisfaction. Furthermore, not only does it affect employee relations but also raises workplace tensions and provides ground to mismanagement and negligence and in some cases fraud (Gkorezis & Bellou, 2016). Liu, Kwan, Lee and Hui (2013) suggest that support from family can lessen the negative effects of ostracism on employee performance by enhancing the employee's ability to cope with feelings of isolation and alienation.…”
Section: Ostracism Employee Performance and Turnovermentioning
confidence: 99%
“…There is also a concern for "excused negligent behavior" which in its nature is an exploitative weakness in the organization formed by ostracism, in this the employees that are ostracized but are not much affected by it, do not perform according to requirement and when confronted on their sub-par performance the excuse that they were not informed or not helped, thus turning themselves from convict to innocent, and continuing their sub-standard performance with little to no repercussions, as they can blame their accountability away (Gkorezis & Bellou, 2016). Furthermore, ostracism is also sometimes seen as an affiliate to certain fraudulent malpractices such as but not limited to, covering tracks, making communication bubbles to delay detection and other malpractices which is a real cause of concern for the organization because if these things remain undiagnosed and not intervened they could have cataclysmically devastating after effects that might become uncontrollable afterwards (Liu & Xia, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Baron and Kenny approach was selected because it is a well-established approach (despite its statistical limitations, e.g. LeBreton et al, 2009) to mediation analysis and has been used across a number of recent studies within the management literature (Cokley et al, 2018;Gkorezis et al, 2014;Gkorezis and Bellou, 2016;Farzaneh et al, 2014;Thompson et al, 2017). This mediation test has several important features.…”
Section: Hypothesis Testsmentioning
confidence: 99%